Bioethics in complexity : foundations and evolutions - De Risio, Sergio; Orsucci, Franco F (Imperial College Press, 2004)
This publication reviews the foundations of ethics in the history of Western thinking. It connects these philosophical matters with evolutionary theory and contemporary bioethics, biology and medicine, posing new questions for the current dialectics between categorical and contextual ethics. Novel answers are presented from complexity theory — self-organization and nonlinear dynamics.
Keywords: bioetika; Bioethics; biologie